Istradefylline: A novel agent in the treatment of "off" episodes associated with levodopa/carbidopa use in Parkinson disease - Lauren Cummins; Marshall E. Cates, PharmD, BCPP, FASHP, FCCP, FALSHP (American Association of Psychiatric Pharmacists, 2022)
The current gold standard for treatment of Parkinson disease (PD) is levodopa/carbidopa (L/C), but long-term treatment frequently results in motor complications, such as wearing-off and motor fluctuations (eg, dyskinesia, "on-off" phenomenon). Istradefylline is a new drug with a unique pharmacologic profile that was approved by the FDA for use as adjunctive treatment to L/C in adult patients with PD experiencing "off" episodes. The drug was shown to reduce "off" time in 4 randomized, double-blind, placebo-controlled studies. The most common adverse effects are dyskinesia, dizziness, constipation, nausea, hallucinations, and insomnia. Unlike many drugs that treat PD, istradefylline is a nondopaminergic drug that exerts its effects via adenosine A2A receptor antagonism. The major drug interactions involve inhibitors or inducers of CYP3A4 as well as tobacco smoking via induction of CYP1A1. Istradefylline is taken once daily as a 20- or 40-mg dose, except in cases involving drug interactions or hepatic impairment. The cost of the drug is relatively expensive, which has implications for Medicare and private insurance coverage. Istradefylline is an alternative option to dopaminergic drugs such as dopamine agonists, monoamine oxidase B inhibitors, and catechol-O-methyltransferase inhibitors as an adjunct to L/C in patients with motor fluctuations, but clinical use will further define its role in treatment of PD.